How does lateral tilting affect the internal strains in the sacral region of bed ridden patients? — A contribution to pressure ulcer prevention. (June 2016) - Oomens, C.W.J.; Broek, M.; Hemmes, B.; Bader, D.L.
Abstract: Background: Repositioning of individuals with reduced mobility and at risk of pressure ulcers is an essential preventive step. Manual or automatic lateral tilting is a way of doing this and the international guidelines propose a 30° to 40° side lying position. The goal of the present study was to determine the internal strains in individuals lying in a supine position and during tilting. Methods: Based on magnetic resonance imaging (MRI) of the sacral area of human volunteers, subject specific finite element models were developed. By comparing calculated contours of the skin, fat and muscle with MRI measurements on a flat surface the models were validated. A parameter study was performed to assess the sensitivity of the model for changes in material properties. Simulations were performed at tilting angles of volunteers between 0° and 45°. Findings: Subjects in a supine position or tilted have the highest strains in the muscle and fat. Tilting does affect the strain distribution, taking away the highest peak strains. There seems to exist an optimal tilting angle between 20° and 30°, which may vary depending on factors such as BMI of the subject and is in the current paper investigated only for the sacrum. Interpretation: The study shows that tilting indeed has a significant, positive influence on internal strains, which is important for the prevention of deep tissue injury. Additional studies are needed to draw conclusions about the greater trochanter area and the tissues around the shoulder. Highlights: Subject specific finite element models were developed based on MRI. Subjects in a supine position or tilted have the highest strains in the muscle and fat. Tilting takes away the highest peak strains. There seems to exist an optimal tilting angle between 20° and 30°. Tilting has a significant, positive influence on internal strains. This is important for the prevention of pressure ulcers.